Dampak Perubahan Iklim Terhadap Kualitas Udara Pada Peternakan Unggas: Systematic Literature Review - Nurhidayah, A F; Syamsuddin, S; Hasrin, H; Hasman, H (PETERPAN (Jurnal Peternakan Terapan), 2024)
The Impact of climate change in poultry farming through increased ambient temperatures. Poor air quality also has serious consequences related to the spread of dust particles and toxic chemicals from poultry waste. The aims this study, based on the description above is to see the relationship between increased ambient temperature and air quality in poultry farms. This study used a systematic literature review method with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. The results obtained from 12 articles related to climate change on air quality in poultry farms. Literature results show that air quality monitoring involves parameters such as NH3, CO2, SO2, NOx, CH4, PM2.5, and PM10 with various measurement methods. The temperature and humidity of the poultry environment are critical to achieving optimal conditions for livestock welfare and growth. Keywords: Air Quality, Climate Change, Poultry, Temperature,